Implementation of open space: the need for uniform policy - Ibrahim, Putri Haryati; Md Dali, Melasutra; Muhammad Yusoff, Safiah @ Yusmah (Canadian Center of Science and Education, 2013)
The provision of open spaces within a residential development is often seen as unimportant. The Malaysian Government targeted to provide 2 hectares of open space per 1000 population to be achieved as a developed nation status by the year 2020. This vision can be seen as the Government attempt to ensure the sustainability of open spaces in Malaysia. The Federal Department of Town and Country Planning, Peninsular Malaysia (FDTCP) has produced a planning standard guideline to supervise the implementation of the open space policy in Malaysia. According to FDTCP; until December 2009, Malaysia has achieved a percentage of 1.19 hectares of open space per 1000 population. Achieving the standard requires commitment of local authorities to implement the open space policy. However, the adoption of open spaces policy differs among local authorities, from a simplistic general approach of land ratio techniques to an ergonomics method. The paper examines the local allocation practices using 5 different approaches and it argues that implementation of open space by local planning practices requires the knowledge of and understanding by planning profession towards a long term sustainable green objectives.